Effectiveness of an educational program for mid‐level Japanese public health nurses to improve program planning competencies: A preliminary randomized control trial - Yoshioka‐Maeda, Kyoko; Shiomi, Misa; Katayama, Takafumi; Hosoya, Noriko; Kuroda, Mariko (Public health Nursing, 2019)
Objective To evaluate the effectiveness of an education program for mid‐level Japanese public health nurses (PHNs) to improve their competencies in program planning, which will fulfill community health needs. Design Randomized control trial. Sample During 2017, 103 PHNs with 5–20 years of PHN work experience in Japan were enrolled and randomly allocated to the intervention (n = 51) or control group (n = 52). Measurements The primary outcome measured competency in program planning based on Competency Measurement of Creativity for PHNs (CMC), knowledge, and skills regarding program planning. Intervention Six web‐based learning modules followed by two face‐to‐face group sessions. Results The PHN participants averaged about 12 years of experience. In the intervention group, 25 PHNs completed all modules (49.0%). Post intervention, there were no statistically significant differences among any between‐group CMC scores. However, the intervention group's CMC 3 score was significantly higher than that of the control group of ≥12 years of experience. Total knowledge and skill scores also improved significantly in the intervention group compared with the control group. Conclusions The results suggest that PHNs with ≥12 years of experience are a suitable target of this educational program, and should play a key role in program planning.